PENGUJIAN PERTUMBUHAN DAN PERKEMBANGAN EMPAT JENIS TANAMAN LEGUMINOSAE PADA TANAH BE:KAS PERTAMBANGAN TIMAH (TAlLING) DI PULAU BANGKA - Siti Nurisjah; , Sahrial; Aris Munandar (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1997)
An experiment to test the growth and development of selected legumes, i.e. Peltophorum pterocarpus DC Heyne (soga), Cassia multijuga Rich. (kasia), Cassia surattensi Burm. f. (galenggang) and Caesalpinia pulcherrima Swartz (kembang merak), on tin tailings was conducted at Tambang Terentang 25, Pangkal Pinang Production Site, Bangka Tin Miningfrom mid March 1989 to January 1990. The four legumes were selected for the facility in obtaining seed, their ability to improve soil fertility, and their ornamental value. The experiment on four legumes on tin tailing, compared to those grown on yellowish brown Podzol association and Bangka podzol, consisted of four parallel trial units based on the randomized block design with three replications. The tests results of 14 weeks of growth indicate the legumes tested, with the exception of Cassia surattensi Burm.f possess an adequate potential to be grown and developed on tin tailing for the improvement of visual quality, vertical and horizontal structure, and ecological function of the lanscape tailing on Bangka Island.